Ricordando Tina Anselmi: la legge sulla parità di trattamento nel Lavoro del 1977 tra il contesto internazionale e la sua soggettività - Alessandro Barbieri è attualmente studente del corso di Laurea Magistrale in Scienze Storiche presso l’Università di Bologna. Ha conseguito la laurea triennale in Storia presso la stessa università, discutendo una tesi in storia moderna dal titolo Alle origini dell’Istituto delle Scienze: l’Accademia degli Inquieti, relatrice Maria Teresa Guerrini. (Diacronie. Studi di Storia Contemporanea, 2018)
After quoting some biographical contributions on Tina Anselmi, the article tries, at first, to propose a biography of her marked by essential moments and, secondly, to trace the instances of the subjectivity of Anselmi in the law on equal treatment in the Work of 1977, inserting the theme in the international context characterized by the debate on the female condition after 1975, International Women’s Year. The last part, finally, is dedicated to the memory of a “mother of the Italian Republic”.